Personal exposure to radio-frequency electromagnetic fields in Europe: Is there a generation gap?. (December 2018) - Eeftens, Marloes; Struchen, Benjamin; Birks, Laura Ellen; Cardis, Elisabeth; Estarlich, Marisa; Fernandez, Mariana F.; Gajšek, Peter; Gallastegi, Mara; Huss, Anke; Kheifets, Leeka; Meder, Inger Kristine; Olsen, Jørn; et al.
Abstract: Background: Exposure to radiofrequency electromagnetic fields (RF-EMF) from mobile communication technologies is changing rapidly. To characterize sources and associated variability, we studied the differences and correlations in exposure patterns between children aged 8 to 18 and their parents, over the course of the day, by age, by activity pattern, and for different metrics of exposure. Methods: Using portable RF-EMF measurement devices, we collected simultaneous real-time personal measurements of RF-EMF over 24 to 72 h in 294 parent-child pairs from Denmark, the Netherlands, Slovenia, Switzerland, and Spain. The devices measured the power flux density (mW/m 2 ) in 16 different frequency bands every 4 s, and activity diary Apps kept by the participants were used to collect time-activity information in real-time. We analyzed their exposures by activity, for the different source constituents of exposure: downlink (radiation emitted from mobile phone base stations), uplink (transmission from phone to base station), broadcast, DECT (digital enhanced cordless telecommunications) and Wi-Fi. We looked at the correlations between parents and children overall, during day (06:00–22.00) and night (22:00–06:00) and while spending time at home. Results: The mean of time-weighted average personal exposures was 0.16 mW/m 2 for children and 0.15 mW/m 2 for parents, on average predominantly originating from downlink sources (47% for children and 45% for parents), followed by uplink (18% and 27% respectively) and broadcast (25% and 19%). On average, exposure for downlink and uplink were highest during the day, and for Wi-Fi and DECT during the evening. Exposure during activities where most of the time is spent (home, school and work) was relatively low whereas exposure during travel and outside activities was higher. Exposure to uplink increased with age among young people, while DECT decreased slightly. Exposure to downlink, broadcast, and Wi-Fi showed no obvious trend with age. We found that exposure to total RF-EMF is correlated among children and their parents (Rspearman = 0.45), especially while at home (0.62) and during the night (0.60). Correlations were higher for environmental sources such as downlink (0.57) and broadcast (0.62) than for usage-related exposures such as uplink (0.29). Conclusion: The generation gap between children and their parents is mostly evident in uplink exposure, due to more and longer uplink and cordless phone calls among parents, and their tendency to spend slightly more time in activities with higher environmental RF-EMF exposure, such as travel. Despite these differences in personal behavior, exposure to RF-EMF is moderately correlated between children and their parents, especially exposures resulting from environmental RF-EMF sources. Highlights: Exposure to RF-EMF from uplink sources is higher in parents than in their children. Diurnal patterns for uplink indicate more phone use between 8 AM and 8 PM. Exposure to RF-EMF is correlated between children and parents from the same family. Higher RF-EMF levels are found in transport, where the uplink contribution is relatively high. The lowest levels are measured at home, school and work, where people spend most time.